PUBLIC SPEAKING DALAM KONTEKS PENGAJARAN - Swestin, Grace; Primasanti, Kartika Bayu (Institute of Research and Community Outreach - Petra Christian University, 2014)
Literatures on public speaking, particularly those in the Indonesian language, often focus on explaining know-hows as well as assuming that public speaking has a universal formula which speakers can abide by. This article argues that public speaking should be studied in particular contexts. It further focuses on the concept of public speaking in a teaching and learning environment. Bearing in mind that public speaking is an indispensable part of academic tradition; this articles—through literature research—attempts to go beyond a practical-centric approach and reviews the connection between the concepts of public speaking and teaching by expounding on the central roles that teacher and student play as speaker and audience.